FORMATION OF THE CONCEPT OF ENTREPRENEURSHIP MANAGEMENT (Development Service Industry Management, 2024)
In the modern conditions of economic development, the special attention of the Government is directed to the development and support of entrepreneurship in Ukraine, because it is successful entrepreneurship that is a catalyst for economic development, which will ensure an increase in the competitiveness of the domestic economy. The state's awareness of the role and importance of entrepreneurship led to the implementation of business support programs, in particular: "eRobot Program"; "One window for international trade"; "support for SMEs"; "Government Office of Ukrainelnvest"; "Action. City"; "Industrial parks". Systemic deregulation is taking place. Regulatory tools are reviewed and then abolished, simplified or digitized, including: credit holidays; tax preferences; support of small and medium-sized businesses; agribusiness support; business information support.In this article, establishes that in the current conditions of economic development, special attention of the Government is directed to the development and support of entrepreneurship in Ukraine. Successful entrepreneurship is a catalyst for economic development, which will ensure an increase in the competitiveness of the domestic economy. The article examines the etymology of the economic categories concept, entrepreneurship, and management. Peculiarities of entrepreneurship management were determined, which made it possible to form the concept of this process. The article analyzes existing concepts of management. It has been established that the complex application of process, system and situational approaches is a priority in the formation of the concept of business management. Based on the results of the research, the main tasks in the field of business management were determined and the concept of business management was formed. The formed concept of business management covers all key areas of business implementation in modern economic conditions. The formed concept of business management covers all key areas of entrepreneurship implementation in modern economic conditions.
Keywords: concept; management; entrepreneurship